O limiar da cidade: modernidade e criollismo em Jorge Luis Borges - Demenech, Pedro (2012)
This essay approaches the modernization of Buenos Aires by the optics of the argentine writer Jorge Luis Borges, during the years of 1920. In this perspective, it presents some of Borges questionings around the years in which Buenos Aires acquired the characteristics of a modern city, as asserted by Beatriz Sarlo. It analyzes, therefore, the way Borges faced the instituting of modernity in Buenos Aires and his criollismo. Another aspect of this essay is the focus on how an urban culture emerged in Buenos Aires by the same time as its consolidation as a political and cultural center in Argentina. As we studied the history of Buenos Aires during the consolidation of its modernization process, we used Jorge Luis Borges work as a source to understand such development in the capital of Argentina.